Perception of members of the Jambi City gymnastics studio toward general gymnastics in the process of weight loss - Kevin Waldo; Ilham Ilham (Institute of Information Technology and Social Science (IITSS), 2025)
This study aims to examine the perceptions of members of the Jambi City Gymnastics Studio regarding General Gymnastics in the process of weight loss. Studio members often face challenges in achieving effective weight loss goals, particularly in terms of motivation, exercise techniques, and understanding the benefits of physical activity. General Gymnastics, which combines various gymnastics movements with an enjoyable and engaging approach, is proposed as a solution to increase member participation and the effectiveness of weight loss programs. This study seeks to explore how General Gymnastics supports gymnastics members in the weight loss process based on several indicators, such as exercise effectiveness, increased motivation, and improved understanding of the weight loss process. Through an interactive approach, members can develop a deeper connection with the training program, experience physical and mental benefits, and cultivate healthy lifestyle habits. The research will employ a qualitative approach, including semi-structured interviews and focus group discussions with studio members. The findings are expected to provide insights into members’ perceptions of General Gymnastics in the context of weight loss, highlight challenges encountered in its implementation, and offer recommendations for the development of more effective exercise programs. This study contributes to a better understanding of innovative training methods and provides practical insights for improving weight loss programs within community settings.